Response bias, recollection, and familiarity in individuals with Highly Superior Autobiographical Memory (HSAM). Issue 6 (3rd July 2019) - Frithsen, Amy; Stark, Shauna M.; Stark, Craig E. L.
ABSTRACT: The current study focused on individuals with Highly Superior Autobiographical Memory (HSAM) and had two main objectives: 1) investigate whether HSAMs have increased recollection performance compared to controls, and 2) investigate whether HSAMs have a reliably different response bias than controls. While previous lab-based recognition tests have shown that HSAMs have normal memory performance, these tests were based on a mixture of both recollection and familiarity. Here, we employed recognition tests specifically designed to separate recollected responses from those based on familiarity. Additionally, we were interested in how HSAMs make their memory decisions. Several studies have shown a great deal of variability between individuals in their response bias. Here, individuals with HSAM and age- matched controls completed a remember/know and a source memory test. HSAMs behaved like controls in both overall and recollection-based memory discrimination. However, HSAMs showed a significantly more liberal response bias, endorsing more items as "old" than controls. These findings contribute to our understanding of how memory processes – especially those related to decision-making – function in those with superior memory abilities and may help elucidate how other (non-HSAM) memory experts make decisions.